Personalising Learning: Do Teachers Use Student Voice and Choice at Secondary School? - ShchevliaginMikhail N.; Koroleva Diana O. (Voprosy obrazovaniya / Educational Studies Moscow, 2024)
The article is dedicated to the modern concept “student voice and choice,” which is an essential component of personalised learning. The research was conducted in the Russian schools that integrated the educational platform with personalised learning methodology, “SberClass.” On the basis of 24 interviews with the teachers the article: 1) indicates teachers’ attitude towards the concept “student voice and choice”; 2) investigates the application of the concept in the teacher practice; 3) analyses what benefits and barriers the teachers perceive in giving students the possibility to express their opinions and choose in the learning. One of the findings is the contradiction between teachers’ positive attitude towards the concept and unreadiness for the realisation in teacher practice at the secondary school.